MATHEMATICAL MODELING OF THE CYLINDRICAL INGOTS HEATING PROCESS IN CHAMBER FURNACE - V. I. Timoshpolskij; I. A. Trusova; D. V. Mendelev (Литьë и металлургия)
The results of mathematical modeling of the cylindrical ingots heating processes in three-dimensional erection are given. This offers interest at carrying out of investigations on choice of technology of high-performance heating in thermal furnaces of machine-building production.